Finding the optimal access for proximal upper limb artery (PULA) interventions: Lessons learned from the PULA multicenter registry. Issue 7 (29th September 2021) - Nardai, Sándor; Zafirovska, Biljana; Pataki, Ákos; Nemes, Balázs; Tóth, Júlia; Deák, Mónika; Kedev, Sasko; Bertrand, Olivier Francois; Pirlet, Charles; Merkely, Béla; Ruzsa, Zoltán
Abstract: Objective: The multicenter proximal upper limb artery (PULA) Registry was created to study the optimal puncture sites for the interventions involving the subclavian, axillary, and innominate arteries. Background: Little is known about the optimal vascular access for PULA interventions, despite the well‐known technical complexity of these procedures. Methods: We performed the retrospective analysis of consecutive patients treated for symptomatic steno‐occlusive disease of the proximal upper limb arteries between January 2015 and December 2019 in three high‐volume centers. Acute thrombotic occlusions were excluded from the study. Results: Two hundred and seventy‐two patients were treated for significant stenosis and 108 for total occlusion. The baseline patient's characteristics were similar, except for the higher median age of the stenotic patients: 68.5 years (31.1; 90.0) versus 64 years (38.0; 86.0) p  = 0.0015. Successful revascularization rate was higher in the stenotic group 93.75% (255/272) versus 86.11% (93/108) p  = 0.0230, while the procedure length 27 min (8; 133) versus 46 min (7; 140) p  = 0.0001 and fluoroscopy times 439 s (92; 2993) versus 864 s (86; 4176) p  = 0.0001 were higher in the occlusion group. The main adverse event rate was similarly low. Dual access was used more often to treat occlusions (60.19% (65/108) vs. 11.40% (31/272) p  = 0.0001) without significantly increasing the complication rate. The safest access was ultrasound‐guided distal radial artery puncture, significantly better than conventional radial access with 0% (0/31) versus 13.6% (18/131) p  = 0.0253 complication. Conclusions: The percutaneous revascularization of proximal upper limb arteries is a safe and effective. Dual access can be applied to increase treatment efficacy, without significantly compromising safety.